The Consumer Versus Innovative Dairy Products - Agnieszka Rybowska; Karolina Gromowska (Scientific Journal of Gdynia Maritime University, 2022)
The market of dairy products is one of the most dynamically developing sectors of food products, offering consumers a broad and continuously growing range of products. Innovative products play an important part in this range, being an answer to changing market trends and expectations of ever more aware consumers. The aim of this study was to learn the consumers opinions and their positions towards innovative dairy products. The study was conducted using the CAWI survey method and an original survey form. The test group was made up of 195 residents of the Pomorski Voivodeship who declared they consumed dairy products. The study demonstrated that consumers consume such products frequently and consider them an important part of their diets. The most commonly consumed were traditional dairy products: butter, UHT milk and cheeses. At the same time, the study participants were positively predisposed towards novelty products. They showed the highest preference for flavoured milk-based drinks, yoghurts with additions, and cheeses with additions. When selecting innovative products, the participants mainly followed the health impact of the products, positive opinions and attractive prices, while promotion and advertisement were the least important. As the preferred location for purchasing such products, the participants specified hyper- and supermarkets, large self-service stores and local neighbourhood stores. The study results may be used in general innovative product management, particularly in planning marketing strategies for innovative dairy products.